Modelling Value at Risk: Evidence from the Saudi Stock Market - Arabi, Khalafalla Ahmed Mohamed; Abdelmageed, Hemeda Mohamed (Archives of Business Research, 2018)
This paper aims to estimate Value at Risk (VaR) of Tadawul All Shares Index of Saudi Stock Market (TASI) over the period January 2004 – December 2017. It applies the following methods, empirical quartile, historical simulation (HS), and percentile, parametric via delta normal, GARCH, IGARCH, Monte Carlo simulation and bootstrapping simulation. It uses 5% and 1% critical value under Normal distribution. Back- testing based on likelihood ratio LR accepted empirical quartile at both five and one percent, while accepting delta normal, historical simulation, percentile, IGARCH, and Monte Carlo at one percent. The worst loss obtained is approximately 4%.